Synchrotron Radiation Useful and Interesting Applications - Joseph, Daisy (IntechOpen, 2019)
In this book, the readers will find chapters exposing them to different, useful applications of synchrotron radiation in various fields of physics, archeology, and biosciences. Different research has been carried out in this field and has conveyed a novel approach to the applications of synchrotron radiation.The chapters are crisp and precise and will motivate students, young researchers, and professionals to carry out research with novel ideas. The authors have successfully tried to convey their ideas in a very simple text. It will be useful for both the novice and those who are currently doing research in this field. I hope it will complete my task of enriching researcher into synchrotron radiation with better applications and also giving students a better platform for understanding the subject.